Impact of alumina and cerium oxide nanoparticles on tailpipe emissions of waste cooking oil biodiesel fuelled CI engine. Issue 1 (1st January 2021) - Dinesha, Pijakala; Mohan, Sooraj; Kumar, Shiva
Abstract: Biofuels are one of the most sought-after renewable energy sources to overcome the current energy crisis in the world. Diesel blended with esters derived from oils has shown appreciable results for its use in compression ignition engines. In this work, B20 (20% biodiesel + 80% diesel by volume) fuel blend comprising 80% diesel and 20% biofuel extracted from waste cooking oil is used as a fuel. Two different metallic oxide nanoparticles (NPs), namely, cerium oxide (CeO2 ) and aluminium oxide (Al2 O3 ) each having size of 30 nm, are dispersed in B20 biodiesel blend and used to investigate their combined influence on engine combustion. Experiments are conducted to study the engine exhaust emissions of a single cylinder four-stroke diesel engine running at constant speed of 1, 500 rpm with varying engine loads. Experiments are carried out with B20 fuel and adding mixtures of CeO2 and Al2 O3 nanoparticles in 50–30, 40–40 and 30–50 ppm, respectively, to B20 biodiesel blend. Responses recorded are the emissions of CO, HC, CO2, NOx and smoke. The results reveal that, on adding the nanoparticles, the engine observed a smooth combustion with reduction in the exhaust emissions compared to neat B20 biodiesel operation. B20 blend with 50 ppm of CeO2 and 30 ppm of Al2 O3 nanoparticles showed lower exhaust emissions compared to other fuel blends. For the best fuel blend, CO, HC, NOx and smoke are reduced by 57.3%, 22.3%, 24.3% and 7.36%, respectively, compared to neat B20 operation.